Computerized control systems in the food industry - Mittal, G.S (Food science and technology (USA), 1997)
Covers the fundamentals and the latest advances in computerized automation and process control, control algorithms, and specific applications essential food manufacturing processes and unit operations. This text highlights the use of efficient process control to convert from batch to continuous operation and enhance plant sanitation. It compares both established and innovative control schemes.